PV Design as an Emergency Power Supply for Website Device - Wirgiyanto, Ignatius Agus Purbhadi (ReTII, 2023)
Websites are one of the educational tools in schools that are important for getting the latest information related of education. Apart from displaying the latest and most accurate student profile and school profile data, it is also needed for online New Student Admissions (PPDB) and an online digital library. A problem that often occurs, especially at SMA Negeri 1 Slawi, Central Java, is frequent electrical power outages due to maintenance or unexpected disruptions which cause information activities via the school website to be disrupted. Frequent power outages result in damage to website server equipment, both hardware and software. Therefore, this research aims to design a Solar Photovoltaic Power Plant (PV) as an emergency power supply for website devices. The methods used are planning electrical power requirements, estimating the duration of backup time, calculating PV components, creating a control system, installing and testing. Designing PV for 600 watts of power and a backup duration for 4 hours, the PV components are 600WP solar panels, 30 A solar charger regulator (SCR), 1000 watt inverter, 2 x 100 AH 12 volt batteries, the control system uses relays and timers. The test results of the control system show that it can work either automatically (interlock) to move the load from PLN electricity to PV when PLN goes out, or vice versa from PV to PLN.. In daytime testing, PV can supply the load stably for more than 4 hours because the power to supply the load is contributed by the battery and sunlight. Testing at night, the PV battery can supply the load for 4 hours 4 minutes before the PV battery runs out.